Correlation Between Macronutrient Intake and Physical Exercise with Muscle Mass and Fat Mass in Male Gym Members - Andreas Orlando; Mury Kuswari; Dessy Aryanti Utami; Erry Yudhya Mulyani; Nazhif Gifari (Sport and Nutrition Journal, 2025)
Background: Body composition, particularly the muscle-to-fat ratio, is an essential indicator of metabolic health and fitness. This study aimed to analyze the relationship between macronutrient intake (energy, protein, fat, carbohydrates) and physical exercise parameters (type, frequency, and duration) with the muscle mass and fat mass percentage in active males at a fitness center. Methods: A cross-sectional design involved 42 male participants (aged 20–40 years) selected through purposive sampling at Master Fitness Club. Macronutrient intake was assessed using a 2×24-hour food recall, exercise data were collected via questionnaires, and body composition was measured using Bioelectrical Impedance Analysis (BIA). Data were analyzed using Pearson and Spearman correlation tests, as well as the Mann-Whitney U test. Results: Fat intake was significantly negatively associated with muscle mass (p=0.003; r=−0.443) and significantly positively related to fat mass (p=0.002; r=0.466). Energy, protein, carbohydrate intake, exercise frequency, and duration were not significantly associated with either variable (p>0.05). Conclusion: Fat intake plays a significant role in influencing body composition among active males. Higher fat intake is associated with decreased muscle mass and increased fat mass, highlighting the importance of managing fat intake to achieve optimal body composition.